Prawa i wolności konstytucyjne a działanie japońskiej policji - Depta, Maria (Koło Naukowe Doktryn Politycznych i Prawnych, Katedra Doktryn Politycznych i Prawnych, Wydział Prawa, Administracji i Ekonomii Uniwersytet Wrocławski, 2016)
The Author of the work addresses the human rights contained in the Showa Constitution and how they have been violated by the activities of the Japanese police. The first part describes the history, structure and preventive actions taken by the Japanese police. Secondly the Author will examine the characteristics of the society that may have an impact on the practices used by officers of the law in Japan. Then take a characterization of Chapter 3 of the Constitution concerning civil rights and freedoms. At last, the most important part will try to list and describe the cases of violations of the Constitution by the police
Keywords: prawa człowieka; policja; Japonia; Konstytucja Showa; Organizacja Narodów Zjednoczonych. Komisja Praw Człowieka